The effects of geological heterogeneities and piezometric fluctuations on groundwater flow and chemistry in a hard-rock aquifer, southern India - Perrin, J; Ahmed, S; Hunkeler, Daniel (My University, 2011)
Crystalline aquifers of semi-arid southern India represent a vital water resource for farming communities. A field study is described that characterizes the hydro-dynamic functioning of intensively exploited crystalline aquifers at local scale based on detailed well monitoring during one hydrological year. The main results show large water-table fluctuations caused by monsoon recharge and pumping, high spatial variability in well discharges, and a decrease of well yields as the water table decreases. Groundwater chemistry is also spatially variable with the existence of aquifer compartments within which mixing occurs. The observed variability and compartmentalization is explained by geological heterogeneities which play a major role in controlling groundwater flow and connectivity in the aquifer. The position of the water table within the fracture network will determine the degree of connectivity between aquifer compartments and well discharge. The presented aquifer conceptual model suggests several consequences: (1) over-exploitation leads to a drop in well discharge, (2) intensive pumping may contribute to the hydraulic containment of contaminants, (3) groundwater quality is highly variable even at local scale, (4) geological discontinuities may be used to assist in the location of drinking-supply wells, (5) modeling should integrate threshold effects due to water-table fluctuations.
Keywords: Crystalline rocks; Heterogeneity; India; Discontinuity; Conceptual model